Preclinical HER-2 Vaccines: From Rodent to Human HER-2 - Lollini, Pier-Luigi; De Giovanni, Carla; Nanni, Patrizia (Frontiers in Oncology, 2013)
Effective prevention of human cancer with vaccines against viruses, such as HBV and HPV, raises the question whether also non-virus related tumors could be prevented with immunological means. Studies in HER-2-transgenic mice showed that powerful anti-HER-2 vaccines, could almost completely prevent the onset of mammary carcinoma. Protective immune responses were orchestrated by T cells and their cytokines, and effected by antibodies against HER-2 gene product p185. Analogous findings were reported in a variety of other cancer immunoprevention systems, thus leading to the definition of oncoantigens, optimal target antigens that are causally involved in carcinogenesis and cancer progression. Prophylactic HER-2 vaccines were also effective in preventing metastasis outgrowth, indicating that concepts and approaches developed for cancer immunoprevention could prove fruitful in cancer immunotherapy as well. The availability of cancer-prone mice carrying a human HER-2 transgene is now fostering the design of novel vaccines against human p185. A further bridge toward human cancer was recently provided by novel immunodeficient models, like Rag2−/−;Il2rg−/− mice, which are permissive for metastatic spread of human HER-2+ cancer cells and can be engrafted with a functional human immune system, allowing for the first time the study of vaccines against oncoantigens to elicit human immune responses against human cancer cells in vivo.